2017
DOI: 10.1002/jcu.22499
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of focal liver lesions: Comparison between kupffer phase of CEUS with sonazoid and hepatobiliary phase of gadoxetic acid–enhanced MRI

Abstract: The overall visibility of FLLs was comparable between the Kupffer phase of Sonazoid-CEUS and the hepatobiliary-phase images of gadoxetic acid-enhanced MRI, with a discrepancy between the two modalities in 18% of the cases. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45:542-550, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The advantage of considering the Kupffer phase washout as a major imaging feature in Sonazoid CEUS is the improved sensitivity of HCC diagnosis in at-risk patients. According to previous Sonazoid CEUS studies, 7.8%–13.0% of histopathologically proven HCCs with nonrim APHE showed washout only in the Kupffer phase and not in the late vascular phase [ 22 23 24 25 26 ]. Therefore, Kupffer phase washout has the potential to diagnose additional cases of HCC compared with late and mild washout.…”
Section: Questions and Recommendationsmentioning
confidence: 99%
“…The advantage of considering the Kupffer phase washout as a major imaging feature in Sonazoid CEUS is the improved sensitivity of HCC diagnosis in at-risk patients. According to previous Sonazoid CEUS studies, 7.8%–13.0% of histopathologically proven HCCs with nonrim APHE showed washout only in the Kupffer phase and not in the late vascular phase [ 22 23 24 25 26 ]. Therefore, Kupffer phase washout has the potential to diagnose additional cases of HCC compared with late and mild washout.…”
Section: Questions and Recommendationsmentioning
confidence: 99%
“…Hatanaka et al (2008) found that SZ-CEUS was superior to CECT in diagnostic sensitivity and accuracy of liver malignancies. Yang et al (2017) considered that there was no significant difference between SZ-CEUS and CE-MRI in the detection rate of FLLs. Zhai et al (2019) compared the effectiveness of Sonazoid and Sonovue in FLL assessment in Chinese patients, and the results revealed that Sonazoid's qualitative diagnostic ability was not lower than that of Sono-Vue and that Sonazoid could also significantly improve image quality in the whole liver scan.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing to conventional B-mode and colour Doppler ultrasound imaging, CEUS has higher efficacy in detection and characterization of FLLs [2,3]. Moreover, CEUS has demonstrated similar diagnostic performance to computed tomography (CT) and magnetic resonance imaging (MRI), with advantages including real-time scanning and no radiation exposure [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%